Social Media Engagement's Impact on Gen Z's Political and Civic Participation and Activism - Hossain, Mohammad Tamzid; Afroze, Sanjida; Authithi, Tasfia Mehanaz (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2025)
This study examines the relationship between the social media engagement of Generation Z (Gen Z) and their political engagement, civic participation, and activism. A convenience sample of 296 Gen Z, was used in Bangladesh to investigate the impact of their social media on their political engagement, civic engagement, and civic activism in a quantitative research study. We used SPSS 29 to perform the analyses in the study to test the hypotheses. The research found that there is a strong and positive relationship between the social media use among Gen Z and their political participation, civic engagement, and activism. The findings can offer interesting information on the manner in which digital platforms, especially social media, influence political and civic involvement among Gen Z. In addition, this study contributes to the growing body of literature on digital citizenship and provides analysis on how virtual spaces could help future generations negotiate political and civic issues.